PENGARUH KUALITAS PELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT DI KANTOR DESA SENDANGAGUNG, KECAMATAN KALIORI, KABUPATEN REMBANG - Mochamad Ilhammudin; Tri Yuniningsih; Rizky Hidayati; Sekar Arum Arjun Syarifah (Institut Riset dan Pengembangan Indonesia, 2026)
This study aims to analyze the influence of service quality and employee performance on public satisfaction at the Sendangagung Village Office, Kaliori District, Rembang Regency. The study used an associative quantitative approach with a survey technique through a questionnaire to the community who had received village services. The study population was 109 people in the period July–September 2025, with a sample of 53 respondents determined using the Slovin formula at a 10 percent margin of error. Data analysis was carried out using multiple linear regression preceded by validity, reliability, and classical assumption tests. The results showed that service quality had a regression coefficient of 0.299 with a significance of 0.077, so it did not have a significant effect on public satisfaction at the 5 percent level. In contrast, employee performance had a coefficient of 0.936 with a significance of <0.001, so it had a positive and significant effect on public satisfaction. The R-square value of 0.513 indicates that 51.3 percent of the variation in public satisfaction can be explained by service quality and employee performance, while the remaining 48.7 percent is explained by other factors outside the model. This study confirms that increasing public satisfaction at the Sendangagung Village Office is more strongly determined by employee performance than service quality, so service improvements need to be prioritized on strengthening the professionalism, work consistency, and responsiveness of village officials.